Atherogenic phenotype remains in elderly diabetic patients. Issue 1 (8th January 2014) - Yoshino, Hiroshi; Hasegawa, Kazuo; Yokono, Koichi; Yoshino, Gen
<x xml:space="preserve">Abstract</x> Aim It is known that plasma low‐density lipoprotein cholesterol (LDL‐C) levels tend to decrease with age. Thus, most elderly diabetic patients often show normal LDL‐C levels. Therefore, the present study was carried out to examine whether elderly diabetic patients show "the atherogenic phenotype" even if their LDL‐C is not elevated. Methods The study participants consisted of 236 patients. They were separated into four groups according to their age (below 64 years and above 65 years) and an association of type 2 diabetes. A total of 88 middle‐aged diabetic, 34 middle‐aged non‐diabetic, 64 elderly diabetic and 50 elderly non‐diabetic participants were enrolled. LDL‐C, small dense LDL‐C (sLDL‐C) were investigated. ANOVA were used for comparison of LDL‐C, sLDL‐C and the sLDL‐C/LDL‐C ratio between the four groups. Multivariate regression analysis was carried out in order to find the independent factors associated with the sLDL‐C/LDL‐C ratio. Results Among the four groups, the LDL‐C of the elderly diabetic group showed lower LDL‐C levels compared with that of middle‐aged diabetic group, although the difference was not significant (128.6 ± 38.7 vs 138.4 ± 35.8 mg/dL). In contrast, sLDL‐C and the sLDL‐C/LDL‐C ratio in the elderly diabetic group were both higher than those of the elderly non‐diabetic group (47.0 ± 24.2 mg/dL and 0.36 ± 0.14 mg/dL, vs 21.4 ± 16.7 mg/dL and 0.19 ± 0.11 mg/dL, P < 0.05). Multivariate regression analysis showed that age, sex, the presence of diabetes mellitus and plasma triglyceride were the independent factors determining the sLDL‐C/LDL‐C ratio. Discussion It is concluded from the present data that the atherogenic phenotype remains in elderly diabetic patients even if their LDL‐C is not elevated. Geriatr Gerontol Int 2015; 15: 34–37.